Os mecanismos de alinhamento de interesses entre desenvolvedoras de software e empresas de serviços de consultoria nas alianças estratégicas contratuais globais - Rocha, Fábio Neves da (2013)
The increasing adoption of enterprise software in Brazil has led domestic market to a higher level of maturity on the usage and exploitation of such technology, first among large corporations, and most recently among medium and small companies as well. It has attracted much attention in the practitioner literature, especially about the capacity of software houses and consulting firms to cooperate in such a way that makes them capable for bringing software innovation to the market. In this sense, this research aimed to identify the mechanisms of alignment of divergent interests among large global consulting firms and global software houses for the introduction of new technologies. It was designed as a qualitative, exploratory and descriptive research, given the gap in the literature on the abovementioned topic, and used the multiple case studies methodology, bringing two cases chosen by convenience that involve six different companies, each of them having one consulting firm, one software house and one customer. The data gathering was based on structured interviews and documents both publicly accessible and accessed upon authorization, having a categorical thematic analysis using predefined categories, along with a cross-case analysis. The research has brought to light 11 mechanisms, both formal and informal, that promote the alignment between software houses and consulting firms in their adaptation processes. In addition to the contributions that complement the existing literature, it has found some elements that contradict it, such as the use of hierarchical escalation, in opposition to mediation or arbitration; or the diversity of the corporate strategy among partners in a co-innovation venture, what was meant to have only product leadership kind of constituents. The research s raw material has just scratched the surface of the complex and dynamic universe of the abovementioned actors. At the end of the paper, there are some reflections that cast possibilities for both exploitation of the material in statu quo, or its expansion in order to broadly understand the strategic alliances relationship among firms of the enterprise application software segment. The collaborative innovation mechanisms, for instance, deserve study under the product development strategy pointof- view, in order to provide practitioners with substance for their R&D planning and policies. The interdependence between software houses and consulting firms is presented as a key factor for longevity and stability of alliances, which on one hand brings a major contribution to the literature in the search for a consistent explanation xii about the durable existence of hybrid organization forms in the markets, and on the other hand gives rise to the need for detailed analysis of the interdependence degree, in order to support the planning and management of the most appropriate governance forms in the process of adaptation. Starting from a better understanding of the mechanisms of interest alignment in contractual strategic alliances in particular on the relationship between software houses and consulting firms a new research agenda can be set for the discovery of the alliance relationship dimensions among the firms in the software industry.